Multiple Plumage Ornaments as Signals of Intrasexual Communication in Golden‐Winged Warblers. (February 2017) - Jones, John Anthony; Tisdale, Anna C.; Bakermans, Marja H.; Larkin, Jeffery L.; Smalling, Curtis G.; Siefferman, Lynn
Abstract: Avian plumage represents some of the greatest diversity in integument coloration of all animals. Plumage signals are diverse in function, including those that allow for assessing potential mates or the mitigation of agonistic interactions between rivals. Many bird species possess multiple ornamental traits that have the potential to serve as multiple or redundant signals. For example, male golden‐winged warblers ( Vermivora chrysoptera ) have brilliant carotenoid‐based yellow crowns, melanin‐based black throats, and structurally based white patches on their outer tail feathers. Using a correlative approach, we investigated whether plumage ornaments have the potential to reliably signal ability to acquire higher quality territory, aggressive response to simulated territorial intrusions, and reproductive success. We found that both crown chroma and tail brightness were significantly related to habitat quality and aggression; more ornamented birds held territories with higher quality habitat and were less aggressive toward simulated conspecific stimuli. Older birds sang less threatening songs than younger birds and were more likely to sing their mate attraction song type (type 1) rather than songs typically reserved for agonistic interactions (type 2). Finally, despite our previous research demonstrating that habitat strongly predicts reproductive success in this warbler population, we found no evidence of a direct link between ornamentation and reproductive success. Overall, these data suggest that younger males, and those with lower quality ornaments, compensate with more aggressive behaviors. Additional research is needed to investigate the dynamics between behavioral traits and ornaments to better understand complex signaling and how golden wing signals function in conspecific interactions (male–male interactions and mate‐choice).